Brachycephalic, dolichocephalic and mesocephalic: is it appropriate to describe the face using skull patterns? - Fernanda Catharino Menezes Franco; Telma Martins de Araujo; Carlos Jorge Vogel; Cátia Cardoso Abdo Quintão (Dental Press Editora, 2013)
The use of a standardized terminology in the medical sciences is essential for both clinical practice and scientific research. In addition to facilitating communication between professionals, it enhances the reliability of comparisons made between studies from different areas, thereby contributing to a higher level of scientific evidence. Examples of attempts made to standardize the terminology in other areas dedicated to the study of craniofacial morphology can be found in the literature. On the other hand, one can find in the orthodontic literature a variety of terms that render the consensus and communication between orthodontists and other researchers even more problematic. As an example, one could cite the use of the terms brachyfacial, mesofacial and dolichofacial, which form part of a cranial index terminology used to describe facial types. Thus, a reflection on the origin and differences of the terms used to describe the human facial phenotype may pave the way toward a consensus regarding the meaning that best represents the craniofacial patterns.